Brand Activities in the Everyday Life of Consumers: Discovering a New Way of Thinking Brands? - André Luiz Maranhão de Souza Leão; Sérgio Carvalho Benício de Mello (RAC: Revista de Administração Contemporânea, 2009)
In spite of the growing importance placed on brands in contemporary marketing, we know little about the way consumers understand and define them. With this in mind, we carried out this exploratory study, with the objective of identifying what consumers say about brands when they interact with one another. To this end, we assume that, in social interactions, the impressions of some interfere with the judgment of others, enabling consumers to define certain brand aspects and express what they think about them. To access consumer brand thought, a communication ethnography was undertaken through participant observation of the interaction of individuals from different social groups in everyday life (Hymes, 1986). This procedure led us to identify 38 brand aspects that we named as brand activities, based on the notion of speech activities, which assumes that what we say are actions (Austin, 1990; Wittgenstein, 2005). Max Weber’s social theory and his typology of social action helped us to understand our research findings. A reflexive approach towards them prompted us to suggest the discovery of a new way of thinking brands, and in order to do this we propose a preliminary framework. Finally, we discuss possible contributions both to academia and brand management.